Léxico sexual na aplicação de encontros online Grindr: abordagem lexicográfica e processos de formação de palavras - Yalta, Edgar (2023)
In this paper we aim to establish an initial lexicographic approach to the sexual lexicon used in the online dating application Grindr, as well as to identify word formation processes present in this lexicon. Methodologically, the research is descriptive in nature. To gather the corpus, we analyze profile descriptions and messaging interactions among users of the Grindr application in Metropolitan Lima (Peru). We present a total of forty five (45) lexical entries and identify primarily word formation processes such as derivation and composition. We conclude that this lexicon constitutes an important linguistic repertoire with a strong capacity to establish similarities, motivated by a conservative society, as well as to derogatorily name or characterize individuals within the same group, which is linked to hegemonic masculinities and segregative aspects.